PCL scaffold combined with rat tail collagen type I to reduce keratocyte differentiation and prevent corneal stroma fibrosis after injury. (April 2022) - Xu, Wenhan; Kong, Bin; Xie, Huatao; Zhang, Jiaqi; Liu, Weijian; Liu, Sheng; Zhang, Yanbin; Yang, Fan; Xiao, Jiheng; Mi, Shengli; Xiong, Liming; Zhang, Mingchang; et al.
Abstract: The cornea is one of the major refractive eye components and could be easily injured. An ineffective healing of corneal stromal wound may cause fibrosis and even loss of vision. Therefore, it is pivotal to prevent corneal fibrosis after injury. In this study, a poly (ε-caprolactone) (PCL) microfibrous scaffold infused with rat tail collagen type I was fabricated to obtain a 3D composite material. Physical and biological properties of PCL/collagen scaffold were evaluated, the effect of PCL/collagen scaffold on the proliferation and differentiation of limbal stromal stem cells (LSSCs) were detected in vitro, the differentiation of keratocytes as well as the expression and arrangement of extracellular matrix (ECM) influenced by PCL/collagen scaffold were investigated in vivo . RNA-sequencing on normal and injured corneas was carried out to find out the differential enriched pathways and gene expression. We discovered that the PCL/collagen scaffold simulated the stromal structure with properties that were most similar to the native cornea, the PCL/collagen scaffold exhibited good mechanical and biological properties. We also observed that the PCL/collagen scaffold reduced keratocyte differentiation. Injured corneas treated with PCL/collagen scaffold exhibited more regular collagen distribution and less fibroblasts and myofibroblasts distribution. By RNA-sequencing, we observed that in injured group, ECM-related pathway was enriched and several ECM-related genes were up-regulated. This study provides evidence that application of PCL/collagen scaffold could be a new therapeutic strategy for corneal injury. Graphical abstract: Image 1 Highlights: PCL/collagen scaffold simulates the stromal structure of the native cornea. PCL/collagen scaffold has excellent mechanical and biological properties. The keratocyte differentiation and fibrosis after injury were inhibited by treated with PCL/collagen scaffold. The expression of fibrosis-related genes were minimized by treated with PCL/collagen scaffold. Non-biological scaffolds can also reduce keratocyte differentiation and collagen secretion during repair.